Scoping study brief – State of climate information services in East Africa - Osumba, Joab J.L.; Recha, John W.M. (2019)
This brief presents the findings of a scoping study on climate information services in East Africa, conducted as a requirement for the Climate Resilient Agribusiness for Tomorrow (CRAFT) Project, under Work Stream 4 on Enabling Environment for Climate-Smart Agriculture (CSA). The purpose was to ascertain the status of climate information services under the ambit of CSA in each of the three East African countries.